Adiabatic Evolution of a System of Four Coupled Flux Qubits; Bulletin of the American Physical Society; Vol. 52, № 1 - Richard Harris; Andrew Berkley; Mark Johnson; Paul Bunyk; Sergei Govorkov; Uchaykin (Uchaikin) S. V. Sergey Victorovich; Murray Thom; Brock Wilson; Jaspaul Chung; Jake Biamonte; Mohammed Amin (2007, 2007)
We report upon experimental results from a system consisting of four flux qubits linked via in-situ sign and magnitude tunable coupling elements. The device was operated as an adiabatic quantum computer to solve NP-complete problems whose solutions are encoded in the groundstate configuration of the qubits. Each qubit was coupled to its own dedicated dc-SQUID in order to measure the state of each qubit, thus allowing for unambiguous identification of the groundstate of the coupled qubit system at the end of a computation. Results will be compared to a quantum model of the system's evolution.